MODELING OF FAILED RISK FACTORS AFFECTING ON NON PERFORMING LOAN TO MSME’S IN PANDEMIC COVID-19 - Luhgiatno Luhgiatno; Rauly Sijabat; Aprih Santoso; Nur Laily; Nurhidayati Nurhidayati (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2022)
The contribution of Micro, Small, and Medium Enterprises (MSME) performance has a strategic role as a buffer for the national economy. The economic crisis that has hit Indonesia several times, including during the COVID-19 pandemic, has hit the MSME sector, so the sector is no longer able to repay its loans. Even though at that time the MSME sector was working to fix the classic problems that hampered it is performance. Departing from this phenomenon, this study examines the results of previous studies to map five exogenous variables, namely debt character factors, financial factors, management factors, operational factors as well as market and marketing factors as explanatory variables that allegedly cause MSMEs to experience the risk of failing to pay credit which has an impact on the poor NPL. The results of the SEM analysis of data from 125 MSMEs in Semarang City affected by COVID-19 showed that the high risk of default experienced by MSMEs was caused by debt character factors, financial factors, management factors, operational factors, and poor market and marketing factors which then impact on increasing the NPL ratio.